Rapid Formation of an Ice Doline on Amery Ice Shelf, East Antarctica. Issue 14 (14th July 2021) - Warner, Roland C.; Fricker, Helen A.; Adusumilli, Susheel; Arndt, Philipp; Kingslake, Jonathan; Spergel, Julian J.
Abstract: Surface meltwater accumulating on Antarctic ice shelves can drive fractures through to the ocean and potentially cause their collapse, leading to increased ice discharge from the continent. Implications of increasing surface melt for future ice shelf stability are inadequately understood. The southern Amery Ice Shelf has an extensive surface hydrological system, and we present data from satellite imagery and ICESat‐2 showing a rapid surface disruption there in winter 2019, covering ∼60 km 2 . We interpret this as an ice‐covered lake draining through the ice shelf, forming an ice doline with a central depression reaching 80 m depth amidst over 36 m uplift. Flexural rebound modeling suggests 0.75 km 3 of water was lost. We observed transient refilling of the doline the following summer with rapid incision of a narrow meltwater channel (20 m wide and 6 m deep). This study demonstrates how high‐resolution geodetic measurements can explore critical fine‐scale ice shelf processes. Plain Language Summary: Surface melting over Antarctica's floating ice shelves is predicted to increase significantly during coming decades, but the implications for their stability are unknown. The Antarctic Peninsula has already seen meltwater driven ice shelf collapses. We are still learning how meltwater forms, flows and alters the surface, and that rapid water‐driven changes are not limited to summer. We present high‐resolution satellite data (imagery and altimetry) showing an abrupt change on East Antarctica's Amery Ice Shelf in June 2019 (midwinter). Meltwater stored in a deep, ice‐covered lake drained through to the ocean below, leaving a deep, uneven 11 km 2 depression of fractured ice (a "doline") in the ice shelf surface. The reduced load on the floating ice shelf resulted in flexure, with over 36 m of uplift centered on the former lake. Simple flexure modeling showed that this corresponds to about 0.75 km 3 of water being lost to the ocean. ICESat‐2 observations in summer 2020 profiled a new narrow channel inside the doline as meltwater started refilling it from a new lake created by the flexure. ICESat‐2's capacity to observe surface processes at small spatial scales greatly improves our ability to model them, ultimately improving the accuracy of our projections. Key Points: Satellite images showed an 11 km 2 depression on Amery Ice Shelf as an ice‐covered lake drained abruptly in winter 2019 forming an ice doline ICESat‐2 and WorldView data show elevation fell as much as 80 m in the depression, amidst 60 km 2 of hydrostatic rebound and uplift over 36 m ICESat‐2 photon data profiled a new meltwater channel, incised when a lake formed by the flexural uplift overflowed into the doline in 2020